2001
DOI: 10.1111/1467-8535.00173
|View full text |Cite
|
Sign up to set email alerts
|

Matching/mismatching revisited: an empirical study of learning and teaching styles

Abstract: He has published widely in the field of learning styles and individual differences in relation to computer-based learning environments. He was co-director of the British Library research project "Information Skills for Studentcentred Learning", and is currently researching individual differences in relation to Internet use. Email: N.Ford@sheffield.ac.uk; tel: +44 114 222 2637; fax: +44 114 278 0300. Sherry Y. Chen is a PhD student at Sheffield University's Department of Information Studies. Her current resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
128
5
12

Year Published

2001
2001
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 213 publications
(158 citation statements)
references
References 14 publications
13
128
5
12
Order By: Relevance
“…The findings also echo the views of Fullerton (2000) and Ford and Chen (2001), which showed that users performed better with a system design matching their preferences, whilst their performance was reduced when the design did not match their preferences.…”
Section: Levels Of Understandingsupporting
confidence: 81%
“…The findings also echo the views of Fullerton (2000) and Ford and Chen (2001), which showed that users performed better with a system design matching their preferences, whilst their performance was reduced when the design did not match their preferences.…”
Section: Levels Of Understandingsupporting
confidence: 81%
“…The area of matching of student and teacher styles has been considered by [43]. They argue that more information is needed on the learning styles of large numbers of students, complemented by research geared to generating new insights into the complex interactions between learners and educators.…”
Section: Match or Mismatch Between Learning And Teaching Stylesmentioning
confidence: 99%
“…Many learning style experts [43], [19], and [38] showed the theory that students will learn more and will enjoy the class experience and environment when they can use their preferred learning styles. In some cases, students are blamed when the classroom activity is not compatible with their way of learning.…”
Section: Match or Mismatch Between Learning And Teaching Stylesmentioning
confidence: 99%
“…Field Independent individuals consulted the user guide for a longer period than FD individuals in the linear version, while FD individuals consulted it for longer in the nonlinear version. In addition, Ford and Chen (2001) conducted an empirical study, in which they developed two Web sites with two different navigation paths: one used a depth-first path and the other one used a breadth-first path. In the depth-first path case, each topic is presented in detail before the next topic, while the breadth-first path gives an overview of all material prior to introducing detail.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…The GEFT derives scores for Field Independence by requiring subjects to locate simple shapes embedded in more complex geometrical patterns. However, a criticism of this approach is that levels of Field Dependence are inferred from poor Field Independence performance (Ford & Chen, 2001). The CSA differs from the GEFT in that it includes two subtests.…”
Section: Research Instrumentsmentioning
confidence: 99%